2014
DOI: 10.1007/s00044-014-1073-2
|View full text |Cite
|
Sign up to set email alerts
|

Didanosine phosphoramidates: synthesis, docking to viral NA, antibacterial and antiviral activity

Abstract: In order to increase the binding energy with haemaglutinin-neuraminidase (HN) protein of Newcastle disease virus (NDV), to improve the membrane permeability and to increase antiviral activity, modified structures of didanosine (ddI) were designed by phosphorylation and substitution with various bio-active amines. The designed derivatives revealed better binding energy values (in between -7.9 and -10.6 kcal/mol) than ddI (-7.3 kcal/ mol) with HN of NDV. The docking simulations were encouraged for synthesis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Didanosine is metabolized intracellularly by a sequence of cellular enzymes to its active part dideoxyadenosine triphosphate, which inhibits reverse transcriptase competitively [ 82 ]. Phosphorylated didanosine derivates are designed [ 29 , 31 , 83 ] to overcome the disadvantages of didanosine, such as a short plasma half-life, low bioavailability, and dose-dependent cellular toxicities; it is unstable in its acidic conditions [ 84 ] and has poor permeability through intestinal epithelium and low oral bioavailability [ 85 ]. In one study, phosphorylated didanosine derivate DDI-10 was chosen from a series of designed derivates and showed antiviral activity against NDV in vitro, as evidenced by a significant reduction in plaque formation and cytopathic effects [ 86 ].…”
Section: Didanosinementioning
confidence: 99%
“…Didanosine is metabolized intracellularly by a sequence of cellular enzymes to its active part dideoxyadenosine triphosphate, which inhibits reverse transcriptase competitively [ 82 ]. Phosphorylated didanosine derivates are designed [ 29 , 31 , 83 ] to overcome the disadvantages of didanosine, such as a short plasma half-life, low bioavailability, and dose-dependent cellular toxicities; it is unstable in its acidic conditions [ 84 ] and has poor permeability through intestinal epithelium and low oral bioavailability [ 85 ]. In one study, phosphorylated didanosine derivate DDI-10 was chosen from a series of designed derivates and showed antiviral activity against NDV in vitro, as evidenced by a significant reduction in plaque formation and cytopathic effects [ 86 ].…”
Section: Didanosinementioning
confidence: 99%
“…Sekhar et al [ 84 ] synthesized phosphorylated nucleosides 202a – 202b from the reaction between compound 201 and the corresponding pyridines ( Scheme 44 ). Both compounds 202a – 202b exhibited better activity on Staphylococcus aureus when compared to standard, Gentamycine.…”
Section: Synthesis Of Pyridine Compounds Containing P Se and B With A...mentioning
confidence: 99%
“…Compound 232 showed 53.3% and 50% reduction with rotavirus Wa strain and adenovirus type 7, respectively. Sekhar et al [ 84 ] reported that compounds 202a and 202b ( Scheme 44 ) exhibited the better antiviral activities against Newcastle disease virus (NDV) in embryonated chicken eggs by vanishing of virus at the sixth titer (1/32). Abu-Hashem et al [ 104 ] reported the synthesis of compounds 234a and 234b by reaction of 233a and 233b , respectively, with triethoxy-methane ( Scheme 54 ).…”
Section: Synthesis Of Antiviral Pyridine Compoundsmentioning
confidence: 99%
“…Previously several researchers proved the NDV inhibitory activity of aminated nucleosides . It was found that amino acid esters are used as pro‐drugs of nucleoside namely Valacyclovir, L ‐valine can easily diffuse across the intestine mediated by the intestinal proton‐coupled peptide transporter which resulted in increase of oral absorption, such as Acyclovir and Ganciclovir …”
Section: Introductionmentioning
confidence: 99%